Gasdermin D deficiency aggravates nephrocalcinosis-related chronic kidney disease with rendering macrophages vulnerable to necroptosis - Yoshihiro Kusunoki; Chenyu Li; Hao Long; Kanako Watanabe-Kusunoki; Meisi Kuang; Julian Aurelio Marschner; Andreas Linkermann; Stefanie Steiger; Hans-Joachim Anders (Cell Death and Disease)
Abstract Several forms of regulated necrosis contribute to the pathogenesis of crystal nephropathy, however, the role of pyroptosis, an inflammatory form of cell death involving the formation of gasdermin-D pores in internal and external cell membranes, in this condition remains unknown. Our transcriptional and histological analyses suggest that Gsdmd in tubulointerstitital cells may contribute to the pathogenesis of chronic oxalate nephropathy. However, genetic deletion of Gsdmd exacerbated oxalate nephropathy in mice in association with enhanced CaOx crystal deposition and accelerated tubular epithelial cell injury. Pharmacological inhibition of necroptosis reversed this effect. Indeed, Gsdmd −/− bone marrow-derived macrophages were more prone to undergo necroptosis when stimulated with CaOx crystals compared to their wildtype counterparts. We conclude that gasdermin D suppresses the necroptosis pathway, which determines the outcome of oxalate nephropathy-related nephrocalcinosis.